ANALYSIS OF THE EFFECTIVENESS AND EFFICIENCY OF REGIONAL TAX REVENUE ON REGIONAL FINANCIAL INDEPENDENCE IN AMBON CITY - Juner Elsyeh Soukotta; Jozef Ricky Pattiruhu; Steven Siaila (SEAN Institute, 2023)
The results show that the R Square value is 0.994 which means that 99% of car demand is jointly influenced by the variables described in the model while the rest is influenced by factors outside the model. Partially, the GDP per capita variable has no effect, the length of the road has a positive and significant effect,